2018
DOI: 10.1007/s00380-018-1125-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term physical activity leads to a significant increase in serum sRAGE levels: a sign of decreased AGE-mediated inflammation due to physical activity?

Abstract: There is growing evidence that low levels of the circulating soluble receptor of advanced glycation end products (sRAGE) are a valuable predictor of cardiovascular disease (CVD). The aim of this prospective study was to investigate the influence of long-term physical activity on serum sRAGE levels. 109 subjects were recruited, and 98 completed the study. Participants were asked to perform exercise within the calculated training pulse for 8 months. The performance gain was measured/quantified by bicycle stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
2
18
0
1
Order By: Relevance
“…23,26 Nevertheless, the exercise intervention increased serum sRAGE in chronic studies. 24,25 Although study duration may play a role on sRAGE concentrations, the results from these studies demonstrate that the effect of exercise on sRAGE serum concentrations is inconsistent, similar to what we observed in our systematic review in response to weight management interventions (diet and bariatric surgery). 2 Therefore, further research is warranted to understand the potential modulator effect of exercise on AGEs and its receptors concentrations.…”
Section: Dear Editorsupporting
confidence: 78%
See 1 more Smart Citation
“…23,26 Nevertheless, the exercise intervention increased serum sRAGE in chronic studies. 24,25 Although study duration may play a role on sRAGE concentrations, the results from these studies demonstrate that the effect of exercise on sRAGE serum concentrations is inconsistent, similar to what we observed in our systematic review in response to weight management interventions (diet and bariatric surgery). 2 Therefore, further research is warranted to understand the potential modulator effect of exercise on AGEs and its receptors concentrations.…”
Section: Dear Editorsupporting
confidence: 78%
“…4 Additionally, we also searched for original articles that investi- (Table 1). [23][24][25][26] Among the acute studies, sRAGE concentrations remained unchanged after the inventions. 23,26 Nevertheless, the exercise intervention increased serum sRAGE in chronic studies.…”
Section: Dear Editormentioning
confidence: 99%
“…However, the maximal oxygen uptake was improved both at 3 and 6 months, which is in line with our study. Recently, Sponder et al (2017, 2018) studied PCSK9 levels in 109 men with cardiometabolic risk factors participating in endurance training for 8 months and found that PCSK9 levels were increased at 2, 6, and 8 months. The reason for the increased PCSK9 levels is unclear since no control subjects were used in the study (Sponder et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Regular physical workout is well known as potent strategy against atherosclerotic processes [1]. Training evolves its beneficial effects by the modulation of numerous (cardiovascular) risk factors, such as the lipid and glucose profile [10,11], and evidently ameliorates the inflammation status [12]. Since CD163 and TWEAK were associated with numerous diseases with inflammation as basic pathomechanism, the influence of training on these biomarkers and their soluble forms, sCD163 and sTWEAK, respectively, is of interest.…”
Section: Discussionmentioning
confidence: 99%